Chancroid: Infeksi Menular Seksual , Chancroid : Sexually Transmitted Infecttions - Jihan Nazirah; Wizar Putri Mellaratna (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Chancroid remains an important cause of the genital ulceration syndrome in the tropics where erythromycin has been the mainstay of therapy.Single dose oral azithromycin or ciprofloxacin and intramuscular ceftriaxone regimens offer advantages in terms of improved patient compliance. There are some data to suggest that HIV seropositive and uncircumcised patients are more likely to fail single dose therapeutic regimens and so these groups of patients need more intensive follow up. WHO recommended syndromic management for genital ulceration includes therapy for both chancroid and syphilis.In those parts of the world where diagnostic facilities exist, the diagnosis of chancroid is normally made by laboratory culture of H ducreyi.The more sensitive DNA amplification techniques remain research tools at the present time